JURIDICAL REVIEW OF THE CRIME OF PLANNED MURDER COMMITTED JOINTLY IN THE BELAWAN DISTRICT (STUDY DECISION NO.2931/PID.B/2021/PN MDN): TINJAUAN YURIDIS TERHADAP TINDAK PIDANA PEMBUNUHAN BERENCANA YANG DILAKUKAN SECARA BERSAMA-SAMA DIKECAMATAN BELAWAN (STUDI PUTUSAN NO.2931/PID.B/2021/PN MDN) - Annasari Harahap, Lesti (UPMI Proceeding Series, 2023)
Judicial review of the criminal act of premeditated murder which was carried out jointly in Belawan District (Decision Study No. 2931/Pid.b/2021/Pn Mdn). The aim of the research is to: (1). How is the application of material criminal law in cases involving criminal acts of premeditated murder committed jointly in Belawan District? (2) What are the judge's legal considerations in handing down a decision regarding the criminal act of premeditated murder which was carried out jointly in Belawan District? The type of research in this paper is direct research that emphasizes juridical and empirical approaches. The data used is secondary data consisting of primary legal materials in the form of statutory regulations such as the Criminal Code in conjunction with Article 55 Paragraph (1) 1st, the Criminal Code and laws. Number 8 of 1981 concerning Criminal Procedure Law and other relevant laws and regulations (2) Legal Considerations by the judge in handing down a criminal decision against the perpetrator of premeditated murder which was carried out jointly in the study of decision no. 2931/pid.b/2021/pn mdn mdn stated that the defendants 1. Ragil Sapta Aji, 2. Buhari Saputra Als Abu (prosecution in separate files), 3. Agus Tamih (Prosecution in separate files), were legally and convincingly proven guilty of committing the crime of "premeditated murder openly and with joint force" as in the second indictment carries a prison sentence of 10 (ten) years. The implication of this research is that the judge does not necessarily rely on the Public Prosecutor's demand letter in imposing a crime, but on two pieces of valid evidence plus the judge's belief.